Cultured bear bile powder ameliorates acute liver injury in cholestatic mice via inhibition of hepatic inflammation and apoptosis. (10th February 2022) - Cai, Jingyi; Wu, Jiasheng; Fang, Su; Liu, Shaoyong; Wang, Tianming; Li, Yuanyuan; Zou, Juan; Shi, Rong; Wang, Zhengtao; Yang, Li; Ma, Yueming
Abstract: Ethnopharmacological relevance: Natural bear bile powder (NBBP) is a traditional Chinese medicine used for treating liver dysfunction. Cultured bear bile powder (CBBP), which is produced using biotransformation of chicken bile, acts as an appropriate substitute for NBBP when treating cholestatic liver injury. Aim of the study: To investigate the molecular mechanisms underlying the hepatoprotective effects of CBBP in an α-naphthylisothiocyanate (ANIT)-induced cholestatic mouse model. Materials and methods: Cholestatic mice were pretreated with CBBP or NBBP via oral gavage once a day for two weeks. Their blood biochemistry and liver histopathology were then evaluated using standard protocols. Western blot analyses, real-time polymerase chain reaction, and immunohistochemistry were used to evaluate changes in the protein levels and gene expression profiles of factors associated with hepatic inflammation and apoptosis in cholestatic mice. Results: CBBP significantly decreased the serum indices of liver injury, and ameliorated neutrophil infiltration and hepatocyte necrosis within liver tissue of cholestatic mice. Expression of the inflammatory factors, such as tumor necrosis factor-α, interleukin-1β (IL-1β), IL-6, monocyte chemoattractant protein-1, and intercellular adhesion molecule 1, was significantly reduced in CBBP-treated cholestatic mice. Moreover, proteins involved in the toll-like receptor 4/myeloid differentiation factor 88/nuclear factor-kappa B (TLR4/Myd88/NF-κB) signaling pathway, such as CD14, TLR4, Myd88, and NF-κB, that were increased in cholestatic mice, were downregulated by CBBP. Meanwhile, increased expression of the apoptosis-related proteins, caspase-3 and Bax, in cholestatic mice was reversed by CBBP treatment. Conclusion: CBBP treatment alleviates ANIT-induced cholestasis and liver injury by reducing hepatocyte inflammation and apoptosis. Graphical abstract: Image 1